Pulmonary aspergillosis in an immunocompromised patient diagnosed with severe COVID-19 in the State of Pará, Brazil (Research, Society and Development, 2025)
Aspergillosis is a fungal infection caused by Aspergillus spp, a saprotrophic fungus found mainly in soil and in residential and hospital environments. This lung disease can affect immunocompromised individuals, and the presence of comorbidities increases susceptibility to fungal infection. Affected individuals may present with recurrent hemoptysis, chronic cough, purulent sputum, recurrent respiratory infections, pleuritic pain, and respiratory distress. The study aims to describe a case of pulmonary aspergillosis in an immunocompromised patient in the state of Pará. This is an observational and descriptive study. The information was obtained through interviews, medical record analysis, and literature review. The correlation between hospitalization, diabetes mellitus, and COVID-19 infection in the context of pulmonary aspergillosis is complex, involving immunological, environmental, and microbiological factors. The patient presented has a history of comorbidities that make him susceptible to fungal proliferation, related to the impairment of the immune system caused by type 2 diabetes mellitus and infections such as SARS-CoV-2.